2016
DOI: 10.1038/srep26486
|View full text |Cite
|
Sign up to set email alerts
|

Multiple host switching events shape the evolution of symbiotic palaemonid shrimps (Crustacea: Decapoda)

Abstract: The majority of the almost 1,000 species of Palaemonidae, the most speciose family of caridean shrimp, largely live in symbioses with marine invertebrates of different phyla. These associations range from weak epibiosis to obligatory endosymbiosis and from restricted commensalism to semi-parasitism, with the specialisation to particular hosts likely playing a role in the diversification of this shrimp group. Our study elucidates the evolutionary history of symbiotic palaemonids based on a phylogenetic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
129
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(143 citation statements)
references
References 46 publications
14
129
0
Order By: Relevance
“…A host switch is therefore more probable, but it is unclear when and where this could have happened, either in the Hawaiian Islands or in more westward localities. Host switches have also been reported from other crustacean taxa, such as pea crabs (Becker and Tü rkey 2017), xanthid crabs (García-Hernández et al 2016), and palaemonid shrimps (Brinkmann and Fransen 2016, Horká et al 2016, Hoeksema and Fransen 2017.…”
Section: Discussionmentioning
confidence: 99%
“…A host switch is therefore more probable, but it is unclear when and where this could have happened, either in the Hawaiian Islands or in more westward localities. Host switches have also been reported from other crustacean taxa, such as pea crabs (Becker and Tü rkey 2017), xanthid crabs (García-Hernández et al 2016), and palaemonid shrimps (Brinkmann and Fransen 2016, Horká et al 2016, Hoeksema and Fransen 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Although several molecular studies were recently constructed (Kou et al 2013, Gan et al 2015, Horká et al 2016) to examine intrageneric relationships of the genus Periclimenes , a full resolution has not been achieved yet, partly due to incomplete coverage of species diversity, partly due to the low basal support of some clades within the analysis. Excluding the species recently allocated to Echinopericlimenes Marin & Chan, 2014 and Bathymenes Kou, Li & Bruce, 2016, only about 25 species of Periclimenes are involved in the analyses representing about 20% from the almost 130 species presently in the genus.…”
Section: Introductionmentioning
confidence: 99%
“…Within marine palaemonid shrimps, it is the most species-rich genus comprising over 150 species (De Grave and Fransen, 2011). However, Gan et al (2015) and Horká et al (2016) suggested that Periclimenes is a polyphyletic taxon on the basis of molecular evidence. High morphological diversity is also shown within the genus, and Periclimenes is divided into some species groups, for instance, Periclimenes obscurus Kemp, 1922, Periclimenes diversipes Kemp, 1922, and Periclimenes iridescens Lebour, 1949 (Bruce, 1989;De Grave and Anker, 2009;Eilbracht and Fransen, 2015).…”
Section: A New Palaemonid Genus Michaelimenesmentioning
confidence: 99%